2009
DOI: 10.3324/haema-tol.2008.000893
|View full text |Cite
|
Sign up to set email alerts
|

Serum Dickkopf-1 is increased and correlates with reduced bone mineral density in patients with thalassemia-induced osteoporosis. Reduction post-zoledronic acid administration

Abstract: Terpos E. Serum Dickkopf-1 is increased and correlates with reduced bone mineral density in patients with thalassemiainduced osteoporosis. Reduction post-zoledronic acid administration. Haematologica 2009; 94:725-728. doi: 10.3324/haematol.2008 This is an open-access paper. ABSTRACTSerum Dickkopf-1 is increased and correlates with reduced bone mineral density in patients with thalassemia-induced osteoporosis. Reduction post-zoledronic acid administration Dkk1 was measured at baseline and after 12 months of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
4
20
1
Order By: Relevance
“…In contrast, placebo group patients showed an increase of sclerostin levels (from 628 ± 534 to 781 ± 429 pg/ml; p = 0.01) and a borderline increase of Dkk-1 (p = 0.08). In our thalassemia patients, after zoledronic acid treatment the correlations between sclerostin and BMD of the studied sites was not significant anymore, while a signifi cant negative correlation was observed between percentage change of Dkk-1 and percentage change of L1-L4 BMD (r = − 0.458, p < 0.01) and R-BMD (r = − 0.512, p < 0.01) in patients who received zoledronic acid, as reported previously [ 4 ] .…”
Section: Control Groupssupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, placebo group patients showed an increase of sclerostin levels (from 628 ± 534 to 781 ± 429 pg/ml; p = 0.01) and a borderline increase of Dkk-1 (p = 0.08). In our thalassemia patients, after zoledronic acid treatment the correlations between sclerostin and BMD of the studied sites was not significant anymore, while a signifi cant negative correlation was observed between percentage change of Dkk-1 and percentage change of L1-L4 BMD (r = − 0.458, p < 0.01) and R-BMD (r = − 0.512, p < 0.01) in patients who received zoledronic acid, as reported previously [ 4 ] .…”
Section: Control Groupssupporting
confidence: 81%
“…Linear regression analysis showed that age was strongly correlated with sclerostin levels (r = 0.759; p < 0.001) independent of the type of the disorder (thalassemia-associated osteoporosis or postmenopausal osteoporosis; p = 0.110). [ 4 ] . There was also a weak correlation between FN-BMD and serum Dkk1 (r = − 0.212, p = 0.072).…”
Section: Control Groupsmentioning
confidence: 95%
“…As previously reported by Voskaridou et al, subjects with TM-induced osteoporosis showed higher values of soluble DKK-1 and sclerostin (which are well-characterized receptor inhibitors of the Wnt pathway in bone) when compared with healthy controls [13,14]. In TM subjects, L1-L4 BMD was positively related to sclerostin, and this could be explained, at least in part, to the higher osteocyte number or osteocyte viability.…”
Section: Discussionsupporting
confidence: 62%
“…This pathway is modulated by a number of factors that include Dickkopf-1 (DKK-1) and sclerostin, which compete with Wnt/ β-catenin for binding to LRP5/6, disrupting (Dkk-1) or antagonizing (sclerostin) LRP5/6-mediated Wnt signaling. Recently, sclerostin and DKK-1 were found to be increased in TM patients, highlighting a possible role of the Wnt pathway in the pathogenesis of TM-induced osteoporosis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The RBD in men is multi-factorial, factors such as advancing age, heredity, hypogonadism, chronic steroid use, alcohol, calcium and vitamin D intake, weight, chronic illness, smoking and restricted physical activity will impact bone mass [2,7]. High incidence of RBD has already been reported in some haematological disorders such as thalassemia and haematologic malignancies [8,9].…”
Section: Introductionmentioning
confidence: 98%